Tharu women at the crossroads of labor migration in Chitwan, Nepal - Grimaldi, Andrea (Himalaya (Portland, Or.), 2022)
In an ethnically mixed village in the Chitwan district of Nepal, large numbers of young Tharu men are migrating for labor to the Arab Gulf countries and Malaysia. Drawing on ethnographic fieldwork, this essay examines the impact labor migration has on the lives of women who stay behind. I focus on two ways that local women participate in this process: first, by financing migration through microcredit loans and second, by managing the remittances they receive from abroad. I argue that, while women now play a significant role in helping finance migration, they are still subject to societal oversight when it comes to managing the remittance money, which creates new sources of conflict within families, and reinforces women’s desires to become more independent. Microcredit loans and remittances, as a social agreement and the material outcome of migration, are altering traditional gender roles, although it is still too early to determine their lasting effect.